Biomimetic self-shading technology for improving building environmental performance: A bibliometric analysis - Salama, Mariam; Shahda, Merhan M.; Eltarabily, Sara; Megahed, Naglaa A. (Edelweiss Applied Science and Technology, 2025)
Biomimetic self-shading (BSS) technology proposes principles derived from natural systems that can improve a building’s energy efficiency, thermal comfort, and environmental performance in hot and dry climates. Based on biological principles observed in nature, this novel approach minimizes energy use and enhances indoor routing parameters. The study aims to review the state of the art in the field of self-shading and its connection with biomimetic science to identify gaps in scientific research. It provides a detailed overview and bibliometric review of BSS, demonstrating its applicability as a morphological approach by investigating building forms and types of self-shading envelopes. The study covers the period from 2014 to 2025, using the Scopus dataset and in-depth analytical tools such as Biblioshiny and VOS Viewer. The results of this review highlight trends in BSS publications and research areas, along with a systematic analysis of BSS design strategies based on the opportunities and challenges of previous studies. The study identifies gaps in the earlier literature, which future studies will address. It confirms that BSS is an effective passive design solution with significant potential for improving environmental performance. Finally, the study concludes with the BSS design strategy to improve environmental performance indicators.